An Approach towards Face Counting System using Image Processing Techniques - Arnob, Sur; Suvro, Sarkar; Kanishka, Sarkar (International Journal of Computer Sciences and Engineering, 2025)
In this modern time, face recognition has gathered much attention and its research has enormously expanded among researchers, since it has many potential applications in computer vision, communication and automatic access control system etc. Especially, human detection is an important part of crowd analysis as the primary goal for automatic human face detection. However, face detection is not very simple as faces of human varies from person to person. They varies in different aspects such as pose variation (front, profile face etc), image orientation, illuminating condition, and facial expression and so on. Therefore, an approach is put forward to evaluate the number of people present in a group image of human. The results found are encouraging.